Hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin: kinetic studies - Diwakar, Makarand M.; Deshpande, R. M.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2005)
The exchange of the Rh/Triphenylphosphine trisulfonate sodium [TPPTS] complex on to an anion exchange resin results in a stable heterogenized catalyst for the hydroformylation of alkenes. The kinetics of hydroformylation of 1-hexene using Rh/TPPTS complex exchanged on anion exchange resin to Amberlite IRA-93 has been investigated for the first time. The rate of the reaction was found to be dependent on the partial pressure of hydrogen and 1-hexene concentrations with a first order. A maximum in the rate with increasing partial pressure of carbon monoxide was observed. A rate model has been proposed which predicts the observed rate data within reasonable error. The activation energy was found to be 84.37 kJ/mol. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogenized catalyst; Hydroformylation; ion-exchange resin; kinetics; Rhodium

Hydroformylation of olefins using dispersed molecular catalysts on solid supports - Pagar, N. S.; Deshpande, R. M.; Chaudhari, Raghunath V. (Catalysis Letters, 2006)
A new method for heterogenization of metal complex catalysts by precipitation of its water-soluble analogue as a Gr.2 metals (Ca, Sr or Ba) salt on porous supports has been proposed. This technique yields a highly dispersed catalyst having a significantly higher activity (TOF) for hydroformylation of olefins compared to other known heterogenized catalysts. The catalyst can be recycled with ease.
Keywords: carbon support; Heterogenization; Hydroformylation; Olefins; Rhodium